EXPLORATORY STUDY OF THE TYPOLOGY OF CONTEXTUAL CHOCOLATE CONSUMPTION EXPERIENCE ON VALENTINE'S DAY - Alvin Natanael Soefian (Perpustakaan Universitas Surabaya, 2019)
The changing in the meaning of Valentine’s Day from the day to honor Saint Valentine death to the day to celebrate love that become a popular culture nowadays. The celebration of Valentine’s Day usually comes along with chocolate as a gift. Chocolate can give various experience for the people who loves chocolate. Thus, this research purpose is to explore the implication of Valentine’s Day meaning to the chocolate consumption experience This research use qualitative approach which use in depth interview to collect data from the informants. Followed by open coding and interpretation to find the implication of Valentine’s Day meaning to the contextual chocolate consumption experience. The informants are categorized as young-adults and the location of the research is in Surabaya. The study found that from the typology of contextual chocolate consumption experience which consist of context of psychological needs, sensorial gratification, memories and nostalgia, escapism, materialism, chocoholism, and interpersonal and self-gift only three that appeared during Valentine’s Day. This can provide future studies to explore different age group and specific type of chocolate. Keywords: Valentine's Day, Typology of Contextual Chocolate Consumption Experience